Sidewalk autonomous delivery robots for last-mile parcel delivery - Strubelt, Henning (Advanced Logistic Systems - Theory and Practice, 2024)
The dynamics of e-commerce, combined with the growing number of users and the increasing volume of last-mile consignments, are driving current developments in logistics. As online commerce continues to grow, so does the need for active service providers to deliver courier, express, and parcel (CEP) shipments on time. Autonomous last-mile delivery is said to have the potential to transform the way we receive goods. As these autonomous delivery technologies continue to develop and become more widespread, it is possible to foresee a future where autonomous delivery vehicles seamlessly navigate our roads and sidewalks, bringing our online orders to our doorsteps faster and more efficiently than ever. After a general classification of sidewalk autonomous delivery robots (SADRs), this paper examines how far the development and implementation of these vehicles have progressed and which developments offer the greatest opportunities for ecological and economic use in the future.